New Design Approach of “3rd - Order Dipole Antenn” Based on Direct Coupled Resonator Bandpass Filter - Alaa K. Al-azzawi (Tamkang University Press, 2021)
An ultra-wideband (UWB) antennas used with the applications of wireless communication systems (WCS), the following five antenna parameters; radiation patterns, directivity, bandwidth, efficiency, and antenna gain should be well optimized. A new design approach based on the coupling matrix theory of synthesis antenna has been presented. The most important parameters of this matrix are; external normalized quality factor, normalized un-loaded quality factor, radiation quality factor, and coupling coefficients between the resonators. Accuracy in calculating these parameters will greatly facilitate control of the antenna bandwidth to be designed. The design approach included a BPF which was also expanded to become an antenna arrays-filter in the hope of increasing the gain and bandwidth of the antenna. Further, a matching unit is placed between the designed BPF and the antenna, to overcome the mismatching situation, and to achieve a high transmission power. The paper presented a new design approach for an active BPF at a frequency “2.45 GHz” and then its integration with a 3rd-order dipole antenna [1]. This design is followed by the creation of another efficient couple-resonant filter (CRF), in which each resonant grid is represented by a radiator. Moreover, a lossless two-port dipole antenna was introduced. Here, each of the poles is integrated with an inductor, to sure that the bipolar antennas can exploit as a resonator. The scores of the simulation sketches and the computed results were convincing. Finally, the performance efficiency of the designed filter at the resonant frequency 2.45 GHz and for both “H-plane” and “E-plan” were summarized in Table 1.